1995
DOI: 10.1177/43.3.7868856
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in hyaluronan synthesis during developing joint cavitation.

Abstract: The mechanisms essential for generating diarthrodial joint cavities between skeletal elements in developing limbs remain enigmatic. Histochemical localization of hyaluronan (HA) at joint interzones concomitant with cavitation led to the postulation that HA may be pivotal in this process. HA synthesis involves the transfer of UDP-glucuronate and UDP-N-acetyl glucosamine to nascent HA by HA synthase. Uridine diphosphoglucose dehydrogenase (UDPGD) activity is responsible for the prior conversion of UDP-glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 24 publications
6
72
0
1
Order By: Relevance
“…Chicks were killed at stage 40 by decapitation (Animal Scientific Procedures act 1986). Limbs were snap-chilled in n-hexane (low in aromatic hydrocarbons, VWR International) maintained below Ϫ70°C, and cryostat sections (10 m) were prepared (4).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chicks were killed at stage 40 by decapitation (Animal Scientific Procedures act 1986). Limbs were snap-chilled in n-hexane (low in aromatic hydrocarbons, VWR International) maintained below Ϫ70°C, and cryostat sections (10 m) were prepared (4).…”
Section: Methodsmentioning
confidence: 99%
“…Controls included omission of primary antibody and replacement of primary antibody with appropriate species-matched normal sera. Alkaline phosphatase activity was disclosed using a filtered solution containing naphthol-AS-MX phosphate, levamisole, and Fast Red TR salt (4). UDPGD activity was assayed using a quantitative cytochemical method as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that HA is indeed a major constituent of developing joint spaces, and our assessment of UDPGD activity in tissue sections indicates that cells directly bordering such cavities possess increased UDPGD activity per cell when compared to cells in the neighbouring epiphyseal cartilage elements. 18,19 This view was recently strengthened by our the of antibodies raised 236 a. a. pitsillides against the N-terminal UDPGD protein that also exhibit a selective labelling of cells at the presumptive line of joint formation in embryonic limbs. We have also shown that these cells exhibit elevated levels of CD44 expression and appear to actively bind HA via a moesin-mediated (CD44-associated actincapping protein) interaction with polymerised cytoskeletal actin.…”
Section: Selective Ha Synthetic Ha-binding Characteristics In Joint mentioning
confidence: 97%